Toward an architecture of enjoyment - Lefebvre, Henri, 1901-1991 (University of Minnesota Press, 2014)
" Toward an Architecture of Enjoyment is the first publication in any language of the only book devoted to architecture by Henri Lefebvre. Written in 1973 but only recently discovered in a private archive, this work extends Lefebvre's influential theory of urban space to the question of architecture. Taking the practices and perspective of habitation as his starting place, Lefebvre redefines architecture as a mode of imagination rather than a specialized process or a collection of monuments. He calls for an architecture of jouissance--of pleasure or enjoyment--centered on the body and its rhythms and based on the possibilities of the senses. Examining architectural examples from the Renaissance to the postwar period, Lefebvre investigates the bodily pleasures of moving in and around buildings and monuments, urban spaces, and gardens and landscapes. He argues that areas dedicated to enjoyment, sensuality, and desire are important sites for a society passing beyond industrial modernization. Lefebvre's theories on space and urbanization fundamentally reshaped the way we understand cities. Toward an Architecture of Enjoyment promises a similar impact on how we think about, and live within, architecture. "--